A generalization of an extended stochastic integral - Albeverio, S.; Berezansky, Yu.M.; Tesko, V.A. (Український математичний журнал, 2007)
We propose a generalization of an extended stochastic integral in the case of integration with respect to a wide class of random processes. In particular, we obtain conditions for the coincidence of the considered integral with the classical Ito stochastic integral.